Opportunities for the development of drowning interventions in West Bengal, India: a review of policy and government programs - M. Gupta; A. B. Zwi; J. Jagnoor (BMC, 2020)
Abstract Background Four million people living in the Indian Sundarbans region in the state of West Bengal face a particularly high risk of drowning due to rurality, presence of open water, lack of accessible health systems and poor infrastructure. Although the World Health Organization has identified several interventions that may prevent drowning in rural low-and middle-income country contexts, none are currently implemented in this region. This study aims to conduct contextual policy analysis for the development of a drowning program. Implementation of a drowning program should consider leveraging existing structures and resources, as interventions that build on policy targets or government programs are more likely to be sustainable and scalable. Methods A detailed content review of national and state policy (West Bengal) was conducted to identify policy principles and/or specific government programs that may be leveraged for drowning interventions. The enablers and barriers of these programs as well as their implementation reach were assessed through a systematic literature review. Identified policies and programs were also assessed to understand how they catered for underserved groups and their implications for equity. Results Three programs were identified that may be leveraged for the implementation of drowning interventions such as supervised childcare, provision of home-based barriers, swim and rescue skills training and community first responder training: the Integrated Child Development Scheme (ICDS), Self-Help Group (SHG) and Accredited Social Health Activist (ASHA) programs. All three had high coverage in West Bengal and considered underserved groups such as women and rural populations. Possible barriers to using these programs were poor government monitoring, inadequate resource provision and overburdening of community-based workers. Conclusions This is the first systematic analysis of both policy content and execution of government programs to provide comprehensive insights into possible implementation strategies for a health intervention, in this case drowning. Programs targeting specific health outcomes should consider interventions outside of the health sector that address social determinants of health. This may enable the program to better align with relevant government agendas and increase sustainability.